2016
DOI: 10.1002/ps.4284
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin inhibitor fromLeucaena leucocephalaseeds delays and disrupts the development ofAedes aegypti,a multiple-disease vector

Abstract: LTI is a promising new tool to control critical points of Ae. aegypti development. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…After 96 h of treatment, larvae were observed visually, and protease inhibitor (BBI and LsCTI)‐treated larvae (Figure C and D) were found to be smaller and to have underdeveloped external structures, such as the cuticle and siphon, compared with the control (Figure A) and LsF5‐treated larvae (Figure B). In agreement with our results, others authors have reported the ability of protease inhibitors, such as LTI and MoFTI, to delay Ae. aegypti larval development.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…After 96 h of treatment, larvae were observed visually, and protease inhibitor (BBI and LsCTI)‐treated larvae (Figure C and D) were found to be smaller and to have underdeveloped external structures, such as the cuticle and siphon, compared with the control (Figure A) and LsF5‐treated larvae (Figure B). In agreement with our results, others authors have reported the ability of protease inhibitors, such as LTI and MoFTI, to delay Ae. aegypti larval development.…”
Section: Resultssupporting
confidence: 94%
“…Similarly, other protease inhibitors did not affect egg hatchability, such as ClTI and the Moringa oleifera flowers trypsin inhibitor (MoFTI) . In contrast, a protease inhibitor from L. leucocephala inhibited egg hatching by 50% in the same conditions . Other classes of proteins have also been reported to inhibit egg hatchability, such as lectins and cysteine proteases …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Toxicity test followed methodology described by Almeida Filho et al ., 30 with slight modifications. Artemia sp.…”
Section: Methodsmentioning
confidence: 99%